Building a Strong Library Association: A Case of the Ghana Library Association - Kofi, Christian (Ghana Library Journal, 2012)
The author explores ways of building a strong library association with specific reference to the Ghana Library Association. The paper states that library associations represent librarians and libraries that provide valuable services to them and their communities. The different types of library associations are discussed. The author provides a historical antecedent to the establishment of the Ghana Library Association in 1962 and looks at the mission, vision and aims. The author then critiques the activities of the Association and identifies factors that should be put in place to build a strong library association. The paper concludes that membership of such a strong library association stands  to derive a host of benefits.